2016
DOI: 10.11648/j.ajaf.20160403.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inorganic Fertilisers and Sunnhemp (<i>Crotalaria juncea</i> [L.]) as a Green Manure Crop on Maize (<i>Zea mays</i> [l.]) Growth, Seed Yield and Labour Cost

Abstract: Maize is the staple food in Swaziland but there have been shortfalls in production mainly due to the high cost of commercial fertilisers. One possible means of addressing the problem is the use of sunnhemp (Crotalaria juncea L.), a green manuring legume, which is cheap and easy to produce. A field experiment was conducted at the Malkerns Research Station during the 2014/2015 cropping season. The main objective of the study was to evaluate whether sunnhemp can be used as a substitute for inorganic fertilisers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Purely green manures sunn hemp (Crotalaria juncea) and velvet bean (Stizolobium aterrimum) have known use in several studies with positive yields in the development of postestablished cultures (Mabuza et al 2016). The forages calopo (Calopogonium mucunoides) and stylo (Stylosanthes spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Purely green manures sunn hemp (Crotalaria juncea) and velvet bean (Stizolobium aterrimum) have known use in several studies with positive yields in the development of postestablished cultures (Mabuza et al 2016). The forages calopo (Calopogonium mucunoides) and stylo (Stylosanthes spp.)…”
Section: Introductionmentioning
confidence: 99%
“…In general, the application of legume green manure (GM) is considered a practical and functional approach to recover soil fertility, because it improves the soil physical S. Mambu et al conditions, supplies nutrients for subsequent plant growth, and stimulates the soil microbial dynamics, such as enzyme activity (Goyal et al 1999, Cherr et al 2006, Kumar et al 2013. Many studies have observed that the incorporation of GM increases the soil organic C, available N, phosphorus (P), potassium, and sulfur contents even in tropical croplands (Sangakkara et al 2004, Bokhtiar & Sakurai 2005, Mabuza et al 2016. However, in Okinawa, GM cultivation is not currently popular, except for in Miyakojima Island, because most local farmers want to conduct ratooning sugarcane cultivation, which is a labor-saving and cost-effective cultivation method.…”
Section: Introductionmentioning
confidence: 99%